Pengaruh Terapi Murottal Al Qur'an Terhadap Nyeri Pada Pasien Luka Bakar - Rantiyana Rantiyana; Miranti Florencia; Suratun Suratun (Universitas Aisyiyah Yogyakarta, 2017)
Objective of the study is to know the effect of Qur’an murottal therapy toward pain of the burned patients in the surgical room at RSUD Prabumulih year 2017. The study used pre-experimental one group pretest-posttest. Population of the study was all the burned patients grade II treated in the surgical room at RSUD Prabumulih. The researcher used nonprobability sampling method with consecutive sampling to select 15 respondents. The results showed that the pain average scale of the patients was 5.73. After getting the murottal therapy, the pain average scale changed into 3.73. The result of paired t-test with p-value 0.001 α = 0.05. There is an effect of Qur’an murottal therapy toward pain of the burned patients in the surgical room at RSUD Prabumulih year 2017.